Global research trend and hotspot in the low FODMAP diet: a bibliometric analysis - Cheng Xu; Zhen Song; Jing-yi Hu; Chong-chao Li; Hong Shen (BMC, 2024)
Highlights The low FODMAP diet is the most recommended dietary intervention for the clinical management of IBS symptoms. Bibliometrics analysis provides a comprehensive perspective and direction on global research trend and hotspot in the low FODMAP diet research. The restriction stage of the low FODMAP diet is superior to other dietary therapies for IBS in terms of symptom response, but it has a negative impact on the abundance of gut Bifidobacteria and diet quality. Identification of biomarkers to predict response to the low FODMAP diet has become the current research hotspot. Large, well-designed clinical research studies are needed in the future to investigate the long-term efficacy and safety of the low FODMAP diet, including FODMAP reintroduction and personalization stages.